Assessment of a sargassum-based liquid biofertilizer for enhanced banana cultivation in small-scale family farms - Yaset Rodríguez-Rodríguez; Laura Isabel Soldevilla-Hernández; Miguel Ángel Guevara; Gustavo Gandini; Ulises Javier Jáuregui-Haza (Case Studies in Chemical and Environmental Engineering, 2025)
The substantial influxes of pelagic Sargassum spp. along Caribbean coasts pose environmental challenges for the region's countries, but also offer opportunities for sustainable valorization. This research develops and evaluates a Sargassum-Based Liquid Biofertilizer (SBLB) produced via anaerobic fermentation, uniquely reducing heavy metal content (e.g., arsenic from 61.6 to 4.08 mg/kg) while retaining beneficial nutrients and microorganisms. This biofertilizer was applied to banana cultivation in Dominican small-scale family farms, SBLB enhanced leaf emission (p < 0.05 in two of three farms) compared to a traditional biofertilizer (BLB) and maintained Black Sigatoka disease below intervention thresholds, matching BLB performance. Chemical and microbiological analyses confirmed SBLB’s safety and efficacy, positioning it as a sustainable alternative to chemical fertilizers. This approach mitigates Sargassum waste and supports organic farming, offering a replicable model for coastal agricultural systems.